Human and animal identity in Philip Pullman's 'His Dark Materials' Trilogy - Husić, Snježana (Array, 2011)
In one of the fantastic worlds devised by Philip Pullman in his trilogy, human characters appear in the company of the daemon, animal-shaped part of their being. Animal characters, on the contrary, do not have their daemon, and some of them crave for one in order to humanize themselves, i.e. to acquire a higher rank in the hierarchy of beings. It thus appears that the narrative adopts contradictory representational strategies with respect to animal: it seems to open a gap between human and animal on one side, and on the other it depicts human as deeply interwoven with the animal. Moreover, the dialectics of this human-animal relationship in the daemon bond undermine the traditional divide between the alleged human rationality and animal instincts.